(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article explores the struggles of the people of Mavaronnahr (present-day Uzbekistan and surrounding regions) to preserve their religious and cultural identity during the Arab and Mongol invasions. It highlights the difficulties faced by the local population in accepting Islam during the Arab conquest and their efforts to maintain traditional beliefs and customs. The article also discusses the heroic resistance during the Mongol invasion, focusing on figures like Jalal al-Din Manguberdi and Timur Malik, who fought to defend their homeland. The concept of “mangurtism” is analyzed in the context of the risk of losing cultural and spiritual heritage. Furthermore, the article touches on the impact of the Russian Empire’s conquest of Central Asia in the 19th century and its influence on the culture, language, and religious values of the local peoples. The importance of studying history, understanding national identity, and preserving cultural heritage for strengthening the future is emphasized